Anaplastic ganglioglioma becoming symptomatic in the third trimester of pregnancy - Pikis, Stylianos; Petrosyan, Tigran; Diamantopoulou, Kalliopi; Kelesis, Christos (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Intracranial tumors are rare in pregnancy and may present a diagnostic and therapeutic challenge. We report on a 34-year-old female who presented with new-onset partial seizures hours following delivery due to a left frontal space occupying lesion. Urgent surgical resection of the lesion was performed and histopathologic evaluation revealed anaplastic ganglioglioma. Post-operatively the patient received radiotherapy and temozolamide chemotherapy. She reported a three-month history of progressive headache and nausea which were falsely attributed to pregnancy both by the patient and her treating physician leading to a delay in diagnosis and management. In the pregnant patient presenting with neurological symptoms a high index of suspicion and a thorough physical examination is required to identify those patients at risk of intracranial pathology.